Pengembangan Minat Wirausaha Berbasis Alam Ecopreneurship Bagi Mahasiswa FISIP Universitas Bhayangkara Surabaya - Fadeli, Muhammad; Prasetijowati, Tri; Ekantoro, Julyanto (Jurnal Pengabdian kepada Masyarakat UBJ, 2025)
Ecopreneurship programs for university students are a strategic approach to fostering entrepreneurial spirit with a focus on environmental sustainability. This initiative integrates urban farming practices with green business innovation by utilizing unused campus land for cultivating productive crops. Through stages of identification, collaboration, training, implementation, and monitoring, the program enhances ecological awareness, entrepreneurial skills, and the development of partnership networks with various stakeholders, including government agencies and conservation communities. In addition to contributing to environmental conservation and local food security, this activity also strengthens the role of educational institutions in supporting the sustainable development agenda. The results of its implementation indicate that urban farming ecopreneurship has significant potential to be replicated and developed as an innovative and contextual learning model with integrated social, economic, and ecological impacts